Locally advanced basal cell carcinoma of the auricle and parotid region: A case report - Milanović Srđan; Stojanović-Rundić Suzana; Milošević Nikola; Dožić Branko; Dožić Marko (Serbian Medical Society - Dental Section, Belgrade, 2021)
Skin cancers are the most common malignant tumors in general. The most significant risk factor is exposure to UV radiation. They mainly occur in the head and neck region, and the majority of about 80% are basal cell carcinomas. Surgery is standard treatment of uncomplicated basal cell carcinomas, but a multidisciplinary approach is necessary in advanced cases. The case report refers to a patient with locally advanced recurrent basal cell carcinoma with primary tumor localization in the right auricle and parotid region in 2012 when primary surgery was performed. Due to the local recurrence, amputation of the right auricle and trepanation of the mastoid process was done in November 2018, and after that, radiation therapy of a recurrent tumor in the area of the trepanation cavity was applied. In the course of follow-up so far, there is good local control, without signs of toxicity. The case report points to the importance of a multidisciplinary approach and the role of radiotherapy in the treatment and control of advanced basal cell carcinoma of this region.